2019
DOI: 10.1111/adb.12826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief inhibition of the ventral tegmental area dopamine neurons on the cocaine seeking during abstinence

Abstract: Preclinical studies strongly suggest that cocaine seeking depends on the neuronal activity of the ventral tegmental area (VTA) and phasic dopaminergic (DA) signaling. Notably, VTA pharmacological inactivation or dopamine receptor blockade in the forebrain may induce behavioral inhibition in general and acute aversive states in particular, thus reducing cocaine seeking indirectly. Such artifacts hinder successful translation of these findings in clinical studies and practice. Here, we aimed to evaluate if dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…A previous report has shown that lowering the activity of VTA dopamine neurons can induce aversive response and behavior [57]. Moreover, Solecki et al have shown that photoinhibition of VTA dopamine neurons reduced the motivation to seek cocaine [58]. Taken together with our result indicating that inhibition of 5-HT projection from the DRN to the VTA is aversive, it is possible that craving-like behavior induced by drugs of abuse may be suppressed by drugs that selectively inhibit 5-HT neurons projecting from the DRN to the VTA.…”
Section: Discussionmentioning
confidence: 98%
“…A previous report has shown that lowering the activity of VTA dopamine neurons can induce aversive response and behavior [57]. Moreover, Solecki et al have shown that photoinhibition of VTA dopamine neurons reduced the motivation to seek cocaine [58]. Taken together with our result indicating that inhibition of 5-HT projection from the DRN to the VTA is aversive, it is possible that craving-like behavior induced by drugs of abuse may be suppressed by drugs that selectively inhibit 5-HT neurons projecting from the DRN to the VTA.…”
Section: Discussionmentioning
confidence: 98%
“…The VTA is one of the major sites of dopamine synthesis. The VTA dopaminergic neurons are implicated in the regulation of emotional and motivational behaviors and are involved in the development of psychopathologies including depression [ 50 ], aggression [ 51 ], and addictions [ 52 , 53 ]. So, it was important to check if the prioritized genes could be implicated in VTA dopaminergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In mESCs, about one fifth of genes are marked by H3K27me3, a repressive histone mark catalysed by Polycomb Repressor Complex 2 (PRC2), which partially resolves through neuronal differentiation 26 (GO:0007611), both critical functions of PGNs 29,30 . Polycomb-classified DN-specific genes in cluster 7 have GO terms including 'response to cocaine' (GO:0042220) and 'response to alcohol' (GO:0097305), highlighting their role in dopamine-receptor responses related to reward-based learning 39,40 . Together, these data suggest that many differentially expressed genes critical for cell specialization can be found within compartment A irrespectively of cell type, and are regulated through specialized mechanisms such as Polycomb repression.…”
Section: Differentially Expressed Genes Are Targets Of Regulation By mentioning
confidence: 99%